Effect of positive and negative symptoms on schizophrenia related quality of life of hospitalized schizophrenic patients at Sargodha and Lahore: Moderating role of neuropsychiatric symptoms - Tehmina kousar; Muhammad Naveed Riaz (Journal of the Pakistan Medical Association, 2020)
Effect of positive and negative symptoms on schizophrenia related quality of life of hospitalized schizophrenic patients at Sargodha and Lahore: Moderating role of neuropsychiatric symptoms